Diagnostic accuracy of GeneXpert vs. fluorescence microscopy on pulmonary tuberculosis: High-burden country - Hatif, Ramlla; Khursheed, Nazia (Infectious Diseases Journal of Pakistan, 2025)
Background: Pulmonary tuberculosis (PTB) is a significant public health challenge in developing countries, and it is one of the leading causes of infection-related morbidity and mortality. Early and accurate diagnosis is crucial for controlling its transmission and improving patient outcomes. Material and Methods: This cross-sectional study was carried out at the microbiology laboratory of Indus Hospital and Health Network, Karachi, from February 1, 2023, to July 31, 2023. A consecutive (non-probability) sampling technique was employed. We performed Xpert MTB/RIF, fluorescence microscopy, and mycobacterial cultures on all pulmonary samples. The sensitivity, specificity, predictive values, and diagnostic accuracy of Xpert MTB/RIF and fluorescence microscopy were calculated and compared with culture as the gold standard. Results: A total of 386 sputum samples were included in the study. More samples tested positive with Xpert MTB/RIF (n = 77, 20%) than fluorescence microscopy (n = 52, 13%). Xpert MTB/RIF demonstrated higher sensitivity (95%) than fluorescence microscopy (64%), while both methods showed comparable specificity (100%) and positive predictive values (100%). The negative predictive value of Xpert MTB/RIF (99%) exceeded that of fluorescence microscopy (91%). Likewise, the diagnostic accuracy of Xpert MTB/RIF (99%) was higher than fluorescence microscopy (97%). Conclusion: The Xpert MTB/RIF demonstrated better diagnostic efficacy, highlighting its importance for prompt and accurate diagnosis of PTB. However, the accessibility and utility of fluorescence microscopy in low-resource settings cannot be overlooked. Keywords: Microscopy, Fluorescence; Mycobacterium tuberculosis / microbiology, Nucleic acid amplification techniques, Predictive value of tests, Tuberculosis, Pulmonary, Sensitivity and specificity